“Efectos del floroglucinol- trimetoxibenceno en la fase activa de labor de parto Hospital regional del Amazonas – Iquitos 1993” - Bartra Alegría, Hortencia (1994)
With the 22.1 percent Escherichia, Estaphylococcus; rn. with the 6.4 per cent ~ Klebsiella. fill. with the 4.4 percent. The complications that frequently arose in women with positive urine culture were: preterm birth in a 22.6 per cent, premature rupture of membranes with e 1 7. 6 percent, a.menaza of preterm delivery with the 6.1 per cent and threatened abortion with e 1 4. 5 por· (e) breach.